Genetic variability of natural Saccharomyces cerevisiae strains - Schuller, Dorit Elisabeth (2007)
Apresentação efectuada no Workshop "Phenomics : advancing high-resolution genome-wide phenotyping in yeast”, Gotenburg, Suécia, Março 2007.